MEASUREMENTS AND CORRELATIONS OF THE VISCOSITY OF ISOPROPANOL MIXTURES WITH DIESEL FUEL AND BIODIESEL - NIȚĂ, Irina; IULIAN, Olga; OSMAN, Sibel; CHIȘ, Timur (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Isopropanol could be an additive or substitute for diesel fuel due to some of its key properties. Viscosity influences the atomization and spray formation, affecting the combustion process and the emission of diesel engine. Experimental data of viscosity of diesel fuel + isopropanol and biodiesel + isopropanol mixtures over the entire composition range at five temperatures (288.15, 293.15, 303.15, 313.15 and 323.15 K) are presented. Based on experimental data, the ability of predictive and correlative models to estimate the viscosity of the studied systems was tested. The best accuracy in viscosity estimation at a desired temperature is given by a polynomial equation, followed by Grunberg-Nissan equation. The value of Grunberg-Nissan interaction parameter G12 increases with temperature increasing, following a trend described by a polynomial equation. Negative values for deviation in viscosity were obtained for diesel fuel + isopropanol mixtures and positive values for biodiesel + isopropanol mixtures. The best fit with viscosity experimental data for viscosity dependence on temperature was provided by Vogel model.